Development of E-Module Acid-Base Based on Problem Based Learning Oriented Chemo-Entrepreneurship to Improve Student’s Critical Thinking Skills - Hanna Salwa Putri; Budhi Oktavia; Yerimadesi; Alizar (Postgraduate, University of Mataram, 2024)
Acid-base is one of the important materials in chemistry learning. Based on preliminary analysis, it is known that students have not properly understood the concept of acid-base. This study aims to develop an acid-base e-module, analyze its validity, practicality, and effectiveness on critical thinking skills. This research method is development research with the Plomp development model. The e-module was validated by 5 valitadors. The practicality test was conducted on 28 students and 3 teachers. The effectiveness of the e-module is seen from the increase in critical thinking test score from 57 students. Validity and practicality were analyzed using Aiken's V, while effectiveness was analyzed with N-Gain. The results showed that the developed e-module had a validity value of 0.89 with a valid category; a practicality value of 0.87 by students and 0.97 by teachers with a practical category. The effectiveness results show that the e-module has an effect on students' critical thinking skills, as evidenced by the N-Gain score of the experimental class of 0,7 with a fairly effective category while the N-Gain score of the control class is 0,4 with a less effective category. Thus, the developed e-module is declared valid, practical, and effective.